Ratio of oxygen saturation index for predicting high-flow nasal cannula outcomes in emergency department for COVID-19 patients with severe hypoxemia: A retrospective study - Cynthia Karam; Ahmad Oseili; Fadia M Shebbo; Mohamad Fakih; Mohamad F El-Khatib (Turkish Journal of Emergency Medicine, 2024)
OBJECTIVES: High-flow nasal cannula (HFNC) oxygen therapy has been used as an initial ventilatory support for coronavirus disease 2019 (COVID-19) patients with mixed levels of acute hypoxemic respiratory failure (AHRF). However, the effectiveness of HFNC when used as initial ventilatory support in COVID-19 patients with severe AHRF exclusively is not well documented. Ratio of oxygen saturation (ROX) index (ROX = [SpO2/fraction of inspired oxygen]/respiratory rate) was shown to predict the outcome of HFNC in intensive care unit patients. Our study aimed to evaluate the utility of the ROX index for predicting HFNC therapy success/failure in COVID-19 patients with severe AHRF when HFNC is used as the first line of ventilatory support. METHODS: Retrospective study in 67 COVID-19 patients with severe AHRF receiving HFNC in the emergency department at a tertiary care academic medical center. ROX index was determined at 0, 2, 6, 12, and 24 h of HFNC onset. The need to escalate to noninvasive or invasive ventilatory support was documented. The receiver operating characteristic curves were performed and areas under the curves (AUCs) were calculated to evaluate the accuracy of ROX index for differentiating between patients who will succeed or fail HFNC therapy. RESULTS: HFNC therapy was successful in 19 patients (28.1%) and failed in 48 patients (71.6%). ROX index after 6 h of HFNC initiation had the best predictive capacity for the outcome of HFNC therapy (AUC = 0.78). ROX index >4.4 at 6 h of HFNC onset was significantly associated with HFNC success/failure. CONCLUSION: ROX index at 6 h after initiating HFNC therapy in COVID-19 patients with severe AHRF has a good predictive capacity for HFNC success/failure.